Inflation and Income Distribution in the United States - Brimmer, Andrew F. (The Review of Economics and Statistics, 1971)
T HE inflation associated with the Vietnam War has had a strikingly differential impact on the rates of economic expansion in different regions of the country and on the distribution of income among major groups in the economy. This experience undoubtedly is of interest to economists concerned with the welfare implications of gains and losses in the relative position of principal groups of income recipients. In addition, these differential effects have enlivened the debate over the appropriate stance of public policies with respect to inflation. Consequently, a comprehensive quantitative examination of the impact of inflation on income distribution during the last decade appears to be a worthwhile undertaking. This paper presents the results of such an inquiry. In section II, the origins of the current inflation (in the Vietnam War) and its subsequent progression are traced. The regional impact of inflation is examined in section III. Broad trends in the distribution of personal income and the main factors affecting this distribution are analyzed in sections IV and V, respectively. The experiences of particular groups of income recipients are assessed in sections VI through IX. Finally, some implications of the findings for public policy are discussed in section X. II The Progression of Inflation